Prenatal diagnosis of a unique scimitar syndrome variant – a case report - Kochanski, Justin; Bardo, Diana; Goncalves, Luis; Lindblade, Chris (Prenatal Cardiology, 2019)
Scimitar syndrome is a rare condition characterised by abnormal pulmonary venous return to the inferior vena cava. It is associated with various cardiopulmonary malformations such as atrial-septal defects, aorticopulmonary collateral vessels, and pulmonary hypoplasia. Diagnosis is typically within the first few months of life. We report a unique case of scimitar syndrome that was diagnosed prenatally using multiple imaging modalities. In addition to two right-sided scimitar veins draining into the suprahepatic inferior vena cava, this patient was found to have horseshoe lung morphology with right pulmonary hypoplasia, a perimembranous ventricular septal defect, sequestered lung tissue, and an aorticopulmonary collateral vessel arising from the descending aorta. The prenatal diagnosis allowed for timely medical and surgical intervention in the postnatal period, which is detailed in this report.